Nanoemulsion Formulation of Kepok Banana Peel Extract and Yellow Watermelon Peel as a Kidney Stone Removal - Diaz Habibah, Khalisha; Ogan Amirudin Lutfi, Dzaka; Thosimomia Tamimi, Nia; Kumala Syifa, Amira; Riska, Erlina; Hidayati, Titiek (Indonesian Health Journal, 2023)
The kepok banana peel and yellow watermelon peel are still rarely appropriately used as medicine. The kepok banana peel and yellow watermelon peel contain flavonoids and potassium that function as kidney stone removers. This study aims to make a nanoemulsion formulation of kepok banana peel extract and yellow watermelon peel as a kidney stone remover. The preparation starts with extraction, testing the flavonoid content of the extract, testing the potassium content of the extract, making nanoemulsion using the homogenization method at a speed of 15,200 rpm, and analyzing the nanoemulsion formula that has been made. This study showed that the nanoemulsion extract contained flavonoids and potassium with a pH value of 7 and a viscosity value of 2.70 cP. The nanoemulsion of kepok banana peel and yellow watermelon peel extracts also has a size of 246.9 nm and a PDI of 0.618 with an oil-in-water (O/W) nanoemulsion type. The extracts of kepok banana peel and yellow watermelon peel in nanoemulsion preparation can be used as a medicine to remove kidney stones.